The Lista APDIS Online: a new vision for an existent service (Journal of EAHIL, 2016)
The Lista APDIS Online (LAO) is a platform for scientific journals in Portuguese health science libraries launched in 2002, allowing efficiency in Inter-library loan services, journals searching, copy requests and their management among institutions. The evolution to a new version was essential. To develop and implement this new platform, the workflow of technical development was defined and the processes of upgrade and migration from the previous to the new database planned. Besides all functionalities of the previous version, the new version has a new database structure, a renewed layout, the ability forf libraries to update their contents and the existence of a user workstation allowing catalog search and requests. Success is predictable by over 1600 orders in only 5 months.